“Because I live it.”: LGB teacher identities, as professional, personal, and political - Llewellyn, Anna (Frontiers in Education, 2023)
Whilst protected by equality laws, lesbian gay and bisexual (LGB) teachers have varying experiences within United Kingdom schools. Schools are predominantly heteronormative, moreover LGB has been positioned as in conflict with discourses of childhood innocence. However, recently there is more expectation of inclusion of diverse gender and sexualities. Although how this is enacted is inconsistent within and between schools. By drawing on interview data conducted in 2020, this research analyses the experiences of LGB teachers. Moreover, it brings together two bodies of literature that do not often speak to each other—research that explores teacher identity and research that centers LGB teacher identity. Findings suggest there are commonalities between these bodies of research, for instance around the importance of ‘being yourself’ and of teachers’ past experiences. However, there is special significance for LGB teachers whose identities have historically been denied in schools, because of their sexual identity. In addition, there is the expectation under neoliberalism of individuals actioning inclusion. As such, the LGB teacher may become a pedagogical resource. None of this is equally available, although marketized notions of diversity place responsibility onto the individual. In their actions, the LGB teacher identity is always professional, personal and political.